The Secret Ingredient in Making a Genius:IIT Bombay - Fulmali, Kanchan S.; Bhasme, Ajinkya P. (SFIMAR Research Review, 2012)
A man of gen/us makes no mistakes; his errors are the portals of discovery. So is it incorrect to say, "Men of genius are often dull and inert in society; as the blazing meteor, when it descends to earth, is only a stone." Because, when a genius comes up with unworldly ideas he explodes like a volcano and single headedly changes the face of humanity. But is a genius born? Or is it a well prepared dish ? There are two kinds of geniuses. The characteristic of the one is roaring, but the lightning is meagre and rarely strikes; the other kind is characterized by reflection by which it constrains itself or restrains the roaring. But the lightning is all the more intense; with the speed and sureness of lightning it hits the selected particular points -and is fatal. And the later are produced by IIT Bombay. In this research paper our main motive has been to find the secret ingredient that IIT Bombay uses to make geniuses. How is Higher Education different in IIT Bombay than many other institutions in the world? Is there some strong bond between Higher education and employability? Methodology: This is the research study of the higher education and the students from IIT-B. So the data collected through the Primary Data- 100 students of IIT Bombay were taken as a sample space; 20 from each branch. And 5 professors of different branches were interviewed to get their feedback. Secondary Data-is collected through the publications like reports of IIT-B, Newspapers, Blogs, various Reference books and Websites. The study throws light on 100% placement of IITians and quality higher education dispensed with an all-round development of students in IIT Bombay. For the comparative study Standard Deviation and Chi-Square methods are used. Hence we conclude that for a bright and secure future, Quality higher education is a must and is as important for learning lifestyle as it is to earn money.